2016
DOI: 10.1002/glia.22962
|View full text |Cite
|
Sign up to set email alerts
|

Sialoadhesin promotes neuroinflammation‐related disease progression in two mouse models of CLN disease

Abstract: CLN diseases are mostly fatal lysosomal storage diseases that lead to neurodegeneration in the CNS. We have previously shown that CD8+ T-lymphocytes contribute to axonal perturbation and neuron loss in the CNS of Ppt1(-/-) mice, a model of CLN1 disease. We now investigated the role of the inflammation-related cell adhesion molecule sialoadhesin (Sn) in Ppt1(-/-) and Cln3(-/-) mice, a model of the most frequent form, CLN3 disease. Microglia/macrophages in the CNS of both models showed an upregulation of Sn and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
61
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 55 publications
(110 reference statements)
10
61
1
Order By: Relevance
“…This led to a mild change in the composition of CD8+ T‐cells upon treatment: while in PLPmut mice 12.19% (±3.15%) of the CD8+ T‐cells were CD8+ CD122+ PD‐1+ regulatory T‐cells, this percentage was nonsignificantly increased to 20.04% (±11.55%; p = .36) after PLX3397 treatment. This change is a likely consequence of reduced numbers of Sn+ microglial cells which have previously been identified to control CD8+ CD122+ PD‐1+ regulatory T‐cells in another disease model (Groh, Ribechini, et al, ).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…This led to a mild change in the composition of CD8+ T‐cells upon treatment: while in PLPmut mice 12.19% (±3.15%) of the CD8+ T‐cells were CD8+ CD122+ PD‐1+ regulatory T‐cells, this percentage was nonsignificantly increased to 20.04% (±11.55%; p = .36) after PLX3397 treatment. This change is a likely consequence of reduced numbers of Sn+ microglial cells which have previously been identified to control CD8+ CD122+ PD‐1+ regulatory T‐cells in another disease model (Groh, Ribechini, et al, ).…”
Section: Resultsmentioning
confidence: 86%
“…Mice were subjected to OCT imaging with a commercially available device (Spectralis OCT; Heidelberg Engineering, Heidelberg, Germany) and additional lenses as previously described (Groh et al, ; Groh, Friedman, et al, ; Groh, Stadler, Buttmann, & Martini, ). Mice were measured at different ages for longitudinal analysis and the thickness of the innermost retinal composite layer comprising nerve fiber layer (NFL), GCL, and inner plexiform layer (IPL) were measured in high‐resolution peripapillary circle scans (at least 10 measurements per scan) by an investigator unaware of the genotype of the mice.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the progress in molecular genetics of the respective disorders, there is presently no cure available to mitigate the severe clinical burden. Since degenerative changes in the retina are diagnostically easily accessible for modern ophthalmologic imaging techniques, like optical coherence tomography, the retina can be viewed as surrogate tissue for these disorders (Bozorg, Ramirez-Montealegre, Chung, & Pearce, 2009;Groh et al, 2013Groh et al, , 2016bGroh, Stadler, Buttmann, & Martini, 2014;Haltia, 2006;Haltia & Goebel, 2013;Weleber et al, 2004). Murine models of both forms have been generated by disrupting the respective genes or introducing the most common human mutation using a "knock-in" approach and mimic the deficits observed in patients (Cotman et al, 2002;Gupta et al, 2001;Mitchison et al, 1999).…”
Section: Neuronal Ceroid Lipofuscinosesmentioning
confidence: 99%
“…Proof-of-principle crossbreeding and bone marrow transplantation approaches have unequivocally demonstrated that neuroinflammation comprising CD81 effector T-lymphocytes amplifies axonal perturbation, neurodegeneration, and clinical features in Ppt1 -/mice (Groh et al, 2013). Moreover, in addition to a pathogenic role of CD81 effector T-lymphocytes, activated microglia/macrophages expressing the proinflammatory cell adhesion molecule Sialoadhesin (Sn) were shown to amplify neural damage and clinical disease in the CLN1 and CLN3 disease models by crossbreeding approaches (Groh et al, 2016b). Moreover, in addition to a pathogenic role of CD81 effector T-lymphocytes, activated microglia/macrophages expressing the proinflammatory cell adhesion molecule Sialoadhesin (Sn) were shown to amplify neural damage and clinical disease in the CLN1 and CLN3 disease models by crossbreeding approaches (Groh et al, 2016b).…”
Section: Neuronal Ceroid Lipofuscinosesmentioning
confidence: 99%
See 1 more Smart Citation